Study of the versatility of CuBTC@IL-derived materials for heterogeneous catalysis. Issue 17 (12th March 2020) - Larrea, Edurne S.; Fernández de Luis, Roberto; Fidalgo-Marijuan, Arkaitz; Maya, Eva M.; Iglesias, Marta; Arriortua, Maria I.
Abstract : The versatility of CuBTC (HKUST-1) MOF materials to be functionalized to improve their catalytic activity performance was evaluated. CuBTC@IL catalysts are selective for the cycloaddition of CO2 to epoxides, giving rise to value-added products. Abstract : The versatility of CuBTC (or HKUST-1) MOF materials to be functionalized to tune their catalytic activity performance was evaluated. The MOFs were functionalized with ionic liquids (ILs) to give rise to catalysts able to adsorb CO2 and react with epoxides to produce carbonates. The materials are active for this reaction and show good conversion rates at 100 °C and 7 bar CO2, confirming their ability to fix this gas and transform it into valuable products. In addition, the MOF@IL composite material 1 can be functionalized to give rise to a bimetallic catalyst, taking advantage of the N-heterocyclic carbene present in the imidazolium-based ILs. Therefore, the material was reacted with palladium dichloride, yielding CuBTC@IL-(NHC)Pd (1Pd ) which has been tested for homocoupling of alkynes and imination of benzyl alcohol reactions. The recyclability of the catalysts has been studied and hot filtration tests have been made.